The regulation of sequence specific NF-κB DNA binding and transcription by IKKβ phosphorylation of NF-κB p50 at serine 80. Issue 21 (10th October 2019) - Smith, Emma L; Somma, Domenico; Kerrigan, David; McIntyre, Zoe; Cole, John J; Liang, Kai Ling; Kiely, Patrick A; Keeshan, Karen; Carmody, Ruaidhrí J
Abstract: Phosphorylation of the NF-κB transcription factor is an important regulatory mechanism for the control of transcription. Here we identify serine 80 (S80) as a phosphorylation site on the p50 subunit of NF-κB, and IKKβ as a p50 kinase. Transcriptomic analysis of cells expressing a p50 S80A mutant reveals a critical role for S80 in selectively regulating the TNFα inducible expression of a subset of NF-κB target genes including pro-inflammatory cytokines and chemokines. S80 phosphorylation regulates the binding of p50 to NF-κB binding (κB) sites in a sequence specific manner. Specifically, phosphorylation of S80 reduces the binding of p50 at κB sites with an adenine at the −1 position. Our analyses demonstrate that p50 S80 phosphorylation predominantly regulates transcription through the p50:p65 heterodimer, where S80 phosphorylation acts in trans to limit the NF-κB mediated transcription of pro-inflammatory genes. The regulation of a functional class of pro-inflammatory genes by the interaction of S80 phosphorylated p50 with a specific κB sequence describes a novel mechanism for the control of cytokine-induced transcriptional responses.